1998
DOI: 10.1073/pnas.95.9.5145
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of rhizobia by acquisition of a 500-kb symbiosis island that integrates into a phe-tRNA gene

Abstract: Nodulation and nitrogen fixation genes of Mesorhizobium loti are encoded on the chromosome of the bacterium. Nevertheless, there is strong evidence that these genes can be transferred from an inoculant strain to nonsymbiotic mesorhizobia in the field environment. Here we report that the chromosomal symbiotic element of M. loti strain ICMP3153 is transmissible in laboratory matings to at least three genomic species of nonsymbiotic mesorhizobia. The element is 500 kb in size, integrates into a phe-tRNA gene, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
364
0
10

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 532 publications
(387 citation statements)
references
References 40 publications
13
364
0
10
Order By: Relevance
“…In contrast to legumes, which are monophyletic (Werner et al 2014), molecular techniques have demonstrated that rhizobia are polyphyletic, belonging to diverse bacterial genera of the Alphaproteobacteria and Betaproteobacteria (Masson-Boivin et al 2009). In RNB, symbiotic ability is conferred by genes for nodulation and nitrogen fixation that can be acquired via lateral transfer of plasmids or genomic islands (Broughton 2003;Freiberg et al 1997;Moulin et al 2004;Nandasena et al 2007;Sullivan and Ronson 1998). To date, 16 rhizobial genera and over 100 species have been validly described (ICSP Subcommittee on the taxonomy of Rhizobium and Agrobacterium-diversity, phylogeny, and systematics; http://edzna.ccg.unam.mx/rhizobial-taxonomy/node/4), and these numbers are expected to increase as more symbioses are studied.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to legumes, which are monophyletic (Werner et al 2014), molecular techniques have demonstrated that rhizobia are polyphyletic, belonging to diverse bacterial genera of the Alphaproteobacteria and Betaproteobacteria (Masson-Boivin et al 2009). In RNB, symbiotic ability is conferred by genes for nodulation and nitrogen fixation that can be acquired via lateral transfer of plasmids or genomic islands (Broughton 2003;Freiberg et al 1997;Moulin et al 2004;Nandasena et al 2007;Sullivan and Ronson 1998). To date, 16 rhizobial genera and over 100 species have been validly described (ICSP Subcommittee on the taxonomy of Rhizobium and Agrobacterium-diversity, phylogeny, and systematics; http://edzna.ccg.unam.mx/rhizobial-taxonomy/node/4), and these numbers are expected to increase as more symbioses are studied.…”
Section: Introductionmentioning
confidence: 99%
“…Such integration events serve to stabilize the auxiliary gene pool, thereby preventing its loss from the population. Most a-proteobacterial genomes also contain genomic islands that carry genes encoding important adaptive traits that can integrate, excise and be transferred across species (Sullivan & Ronson 1998).…”
Section: Rho Dob Act Er Sph Aer Oid Es Pa Ra Co CC Us De Nit Rif Icamentioning
confidence: 99%
“…Recently, an alternative structure for horizontal gene transfer has been found for pathogenicity and symbiosis. These determinants were often detected as so-called pathogenicity and symbiosis islands on the chromosome 12,16,28) . These islands, ranging from 12 to 611 kb in size, are flanked by insertion elements and short direct repeats, and often lie within specific tRNA genes 12,16,28) .…”
mentioning
confidence: 99%
“…These determinants were often detected as so-called pathogenicity and symbiosis islands on the chromosome 12,16,28) . These islands, ranging from 12 to 611 kb in size, are flanked by insertion elements and short direct repeats, and often lie within specific tRNA genes 12,16,28) . Gene transfer among bacteria has been studied for over half a century, but its importance and the mechanisms involved in natural environments still need further investigation, because most studies have been carried out under controlled conditions in microcosms containing specific donors 31) .…”
mentioning
confidence: 99%
See 1 more Smart Citation